Beyond the classroom: how parents view motivation as a key to self-directed learning in township schools - Siziba, Tebogo; Geduld, Bernadette; Du Toit-Brits, Charlene (Frontiers in Education, 2025)
Numerous researchers have emphasized the critical role of self-directed learning (SDL) in education, particularly in township schools, where academic challenges contribute to high failure and dropout rates. Learner struggles are often associated with a lack of motivation and self-direction. In SDL, motivation is related to more than just doing well in school. It is also linked to being resilient, being able to solve problems and being able to change to different learning settings. Recent studies on academic motivation among South African learners reveal the adverse impact of low motivation on energy levels, perseverance, and the pursuit of academic goals. Research on the influence of motivation on SDL in township school contexts, particularly from the perspective of parents, is limited. In response to the imperative for lifelong learning, researchers advocate for the integration of SDL into classrooms. This research investigates the nexus between motivation and the development of self-directed learners in township secondary schools of the lower quintile. Situated within an interpretivist research paradigm, this qualitative study engages parents or legal guardians to explore their perceptions of the role of motivation in the development of learners’ SDL in township schools. The study explores both internal and external motivators that influence learners’ SDL skills to ensure that effective learning can take place. Using a purpose-orientated and convenient sampling, 10 parents or guardians of two schools in Gauteng were selected. Semi-structured face-to-face interviews facilitated data collection and inductive thematic analysis was used. The findings revealed that parents have high expectations of their children’s academic success, believe in their children’s intrinsic drive, and provide comprehensive support. However, motivation alone does not ensure SDL; rather, it must be supplemented by properly defined learning techniques, access to resources, and organized help (from parents and teachers). Hindered by factors such as late working hours and limited educational knowledge, parental involvement was limited. Teacher-learner and parent–child relationships supporting motivation for self-directedness were also lacking. These imply that to improve SDL in township schools, a comprehensive approach is important that combines parental direction, teacher participation, and learner-driven strategies. The findings of this study contribute to a broader discourse on motivation and SDL, highlighting the need for targeted interventions to support learners in township schools.